The Influence of Health Education with Panthom Media about Breast Care on Knowledge and Behaviour in Postpartum Mothers - Rahayu, Ani Muji; Ayuningtyas, Ayuningtyas; Chunaeni, Siti (Midwifery and Nursing Research, 2024)
Background : Breast milk dams are swelling of the breast due to narrowing of the milk ducts due to curdled milk that blocks the duct cavity. Health workers who provide breast care education to postpartum mothers are very useful in increasing their knowledge and ability to carry out postpartum breast care independently. The aim of this research is to examine the impact of health education using pantomime on breast care knowledge and behavior in postpartum mothers.Methods : Participants in this study consisted of 30 mothers during the postpartum period. The sample approach used is total sample. The data obtained were analyzed using the Wilcoxon test. This research uses health education through pantomime media as an independent variable, while education and behavior as dependent factors. This intervention includes conveying health information to women during the postpartum period. Before and during the provision of health education, participants were asked to fill out a questionnaire covering knowledge and practices related to breast care.Result : Before the intervention 16 people (53.3%) had less knowledge, while after the intervention 30 people (100%) had good knowledge. Then it can be concluded that there is a difference before and after the intervention. Breast care behavior in respondents before the intervention was good value 19 people (63.3%), while after the intervention became 23 people (76.7%). Wilcoxon test on knowledge of sig value results. 0.000 0.05, while in behavior the results of the sig value. 0.000 0.05.Conclusions : Health education with panthom media about breast care affects the knowledge and behavior of postpartum mothers. Keywords : Panthom ,Breast Care, Puerperium, Knowledge, Behavior